Optimization of achievement motivation to improve long jump performance - Sin, Tjung Hauw; Ruslin, Budi Indra (COUNS-EDU: The International Journal of Counseling and Education, 2018)
This study aims to reveal the achievement motivation of the athlete's long jump ability. This is so motivated by the observations of the athlete's performance is still not under the reality. Achievement of an athlete long jump is still lower than the previous year and declines. One reason is the low motivation of athlete achievement. This phenomenon is an attraction for writers to examine related to the optimization of achievement motivation to improve the performance of long jump athletes. This research is the quasi-experiment. Sampling is done by purposive random sampling. The sample size was 32 people out of 58 athletes. Achievement motivation data got through the use of instruments in the form of a questionnaire. Validity analysis is to test using product-moment correlation SPSS version 20.00 and data analysis with T-Test. The results showed that there was a significant difference in ability of long jump athletes with high achievement motivation compared to low achievement motivation.